DISEASES OF THE CHILDHOOD AND AND MEDICAL EVENTS WITH THEM PSYCHOLOGICAL EVENTS - M. Pulathajaeva (Innovate Conferences, 2025)
This article discusses the condition of conducting, complications of school-age children and neurographiiological disturbances and the range of examination of medical and technical measures taken to these children.
Keywords: Neverfiology, apathy, adamamia, hypersidine, hypipetic, affective, vegetative symptoms, central nervous systems.